Separate notes on business law within the framework of the passport of scientifc speciality 5.1.3 «Private law (civilistic) sciences» - Kvanina, Valentina V. (Journal of the Belarusian State University. Law, 2022)
The analysis of the new list of the scientifc specialities in legal sciences revealed methodological mistakes in the selection of criteria in a new system of scientifc specialities. The case of business law highlights the defciencies of scientifc speciality 5.1.3 «Private-legal (civilistic) sciences». Shortcomings expressed in artifcial separation of private- and public-legal regulation of entrepreneurial activity, introduction into the categories of scientifc speciality such category as economic activity in the absence at the legislative level of its conceptual and substantive essence, the removal of certain scientifc directions on business law outside the list of scientifc speciality. The author assumes that these miscalculations will not allow to achieve the goal of reforming scientifc specialities in the legal sciences, focusing on complex intersectoral and interdisciplinary scientifc research.